America's national parks : the spectacular forces that shaped our treasured lands - Schullery, Paul. (New York : D.K. Pub., 2001)
Describes U.S. national parks and the environmental factors that shaped the lands, including profiles of Voyageurs National Park in Minnesota, Olympic National Park in Washington, and Acadia National Park in Maine.
"A Tehabi book."
"Discovery Channel."
Includes index.
Keywords: National parks and reserves -- United States -- Pictorial works; Natural history -- United States -- Pictorial works; United States -- Pictorial works